Information Technology Governance Using the COBIT 2019 Framework in Manado Post Companies - Tangka, George Morris William; Lompoliu, Erienika (SEULANGA SYSTEM PUBLISHER, 2024)
Technological advances have brought the world into a new era, including in the field of information. In this context, information technology can be considered useful for supporting and improving company management so that it can compete. One of the information technology management methods that is widely used is IT governance contained in COBIT (Control Objective for Information and Related Technology) 2019. Until now, no evaluation or research has been carried out on Manado Post's IT performance so it is not yet possible to know the level of maturity. application of information technology at Manado Post. This project focuses on using information systems and IT from Manado Post to manage operations and data from Manado Post. This project was carried out by conducting a literature study on COBIT 2019 factor design. Manado Post has identified priority objectives in the COBIT 2019 toolkit, especially EDM03 and APO03. Even though it has reached level 2 capability for EDM03, there are still activities that have not been realized, while for APO03, achievements have not yet reached level 2, indicating the need for improvements in identifying goals and stakeholders as well as aligning architectural goals with strategic programs. Suggestions include in-depth analysis of unrealized sub-objectives, benchmarking with similar organizations, and the development of clear follow-up plans to improve Manado Post's practices in risk management and enterprise architecture.